Teaching Second Language through Green Pedagogy in the Context of Bangladesh: A Methodological Approach - Mst. Dilruba Papi; Md. Nazmul Haque (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
Bangladesh is one of many such countries that are in immediate need to imply concepts of environmental to deal with crises like water, climate change, and so on. Green pedagogy is a permanent process in which individuals and communities become aware of their environment and learn the knowledge, values, skills, and determination to act individually and collectively to solve present and future ecological problems. The purpose of the incorporation of ecological education into teaching English language is to raise ecological awareness of global ecological problems. To be able to take part in this solution process English language learners should especially have critical thinking and critical reading skills. Ecological education practices can be incorporated in English language teaching by fostering critical skills with the suggested approach and authentic texts on ecological issues can be used as classroom material for this purpose. Thus there is a need for a practical framework to guide teachers in the effective implementation of environmental and sustainability concepts in English as a second language.Keywords: Teaching, second language, green pedagogy, sustainability, environment, BangladeshÂ